Efficient and Accurate Optical Signal Processing and Digitization System for High Speed Data Acquisition and Analysis - Sharma Ishaan; Sharma Kadambari (ITM Web of Conferences, 2023)
The evolution of optical fiber technology has expanded its utility beyond communication to encompass measurement. Key components include the light source, detection elements, and processing circuits. This paper describes a system for optical signal processing and digitization of light pulses, employing advanced components to enhance data acquisition and analysis performance. The optical signal processing phase employed the LF356N operational amplifier, offering attributes like low bias current, high bandwidth, and rapid settling time. Configured as a transimpedance amplifier, the opamp transformed light signals into corresponding analog voltage signals. Subsequently, the voltage signal underwent digitization using the AD976AN, a 16-bit ADC with advanced features such as high-speed data acquisition and an integrated clock. This ADC was controlled by a Teesny 3.6 board with a fast CPU clock speed of up to 256 MHz, greatly facilitating rapid data analysis and algorithm execution. The hardware circuit underwent meticulous design, simulation, and fabrication, followed by rigorous testing involving various distinct light sources with differing parameters. The digitized and computed parameter values (obtained after subjecting the ADC outputs to the suggested algorithm) exhibited a high degree of similarity in comparison to the observed values on the oscillo-scope.